The Efficacy of Two Novel Retreatment Systems in the Removal of Root Canal Obturating Materials (An In vitro Study) - Sameh, Rasha; Omaia, Mohamed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The complete removal of root filling material is one of the main goals of non-surgical endodontic retreatment. Thus, the development of new techniques and instruments aiming to promote this task presents clinical significance. AIM: The purpose of the study was to assess the amount of residual root canal filling materials (gutta-percha/sealer) after using two different endodontic retreatment systems and ultrasonic tip. METHODS: Forty-five mandibular premolar teeth were mechanically instrumented and obturated. Retreatment was performed using two different Endostar RE (Group 2), Rogin retreatment system (Group 3), and ultrasonic tip (Group 1). Roots were separated buccolingually into two halves. A digital camera connected to the stereomicroscope captured images to each half. Image-J software was used to evaluate and measure the areas with remaining filling material in each third (cervical, middle, and apical). RESULTS: Data analysis revealed significant differences between the groups in the coronal, middle, and apical thirds (p < 0.05). The ultrasonic retreatment tips (G1) were significantly more efficient in removing the gutta-percha and sealers compared to the Rogin (G3) and Endostar (G2) retreatment endodontic kits. CONCLUSIONS: All the file systems left some filling material in the canals. Ultrasonic retreatment tip had maximum efficacy for the removal of filling materials in comparison with the retreatment file systems under investigation.